Borrowers' Perception regarding Bank Credit-An Opinion Survey of Public, Private and Foreign Bank - Kaur, Kulpreet; Kaur, Rajinder (Gyan Management Journal, 2015)
Bank credit has its vital importance in the perspective of development and growth with social justice. Apart from the quantum of bank credit, its development, competition and direction is equally "1portant in the realization of country's economic goals. Banks create money in the economy by :: jvancing loans to different categories of borrowers for a wide variety of purposes. The present paper .: =tempts to study the demographic profile of the respondents of selected bank groups, problems in .:,:ailing and repaying the loan, opinion of the respondents with regards to agreement statements, ,·1tisfaction statements and overall opinion and their interrelationship with demographic factors . . .:.11alysis revealed that majority of the respondents got their loan without any difficulty. The agreement ,:atements reveal inter-bank differences among the respondents of scheduled commercial banks. The ;atisfaction level of the respondents observed inter-bank differences exist among the respondents of ,cheduled commercial bank with regards to the all satisfaction statements except knowledge of the ,taff and grievance handling system of the bank. The overall opinion of the respondents reveals that "1ajority of the respondents were satisfied with the Joan services provided by the bank. Opinion of the
Keywords: Bank Credit; Scheduled commercial banks; AgreementLevel and Satisfaction Level